"The petals and thorns" of ROSE (rapid on‐site evaluation). Issue 1 (3rd July 2012) - da Cunha Santos, Gilda; Ko, Hyang‐Mi; Saieg, Mauro Ajaj; Geddie, William R.
<x xml:space="preserve">Abstract</x> In this article, the authors discuss the advantages ("petals") and disadvantages ("thorns") of rapid on‐site evaluation (ROSE) performed for minimally invasive procedures such as computed tomography (CT)‐guided and endoscopic‐guided fine‐needle aspiration with a focus on deep‐seated lymph nodes. One of the main advantages is increased diagnostic accuracy. Disadvantages include the need for highly trained professionals and a lack of adequate reimbursement.